2010
DOI: 10.1038/labinvest.2010.95
|View full text |Cite
|
Sign up to set email alerts
|

IFN-κ, a novel type I IFN, is undetectable in HPV-positive human cervical keratinocytes

Abstract: Interferons (IFNs) are expressed by many cell types and play a pivotal role in the generation of immune responses against viral infections. IFN-k, a novel type I IFN, displays a tight tropism for keratinocytes and specific lymphoid populations and exhibits functional similarities with other type I IFNs. The human papillomavirus (HPV), the etiological agent for cervical cancer, infects keratinocytes of the uterine cervix and has been shown to directly inhibit the IFN pathway. We evaluated IFN-k, -b, and -g gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 40 publications
5
43
0
2
Order By: Relevance
“…Our analyses revealed that the constitutive transcription of IFN-is inhibited in HPV-positive keratinocytes, which is consistent with recent in situ analyses of HPV-positive biopsy specimen material and findings in HPV-positive cervical cancer cells (12,37). Since a good correlation between ISGs reduced in HPV-positive cells (Table 1) and ISGs induced by IFN-in HPV18-positive cells can be observed, we postulate that the major cause for the reduction of ISGs in HPV-positive cells is the inhibition of IFN-transcription.…”
Section: Discussionsupporting
confidence: 92%
“…Our analyses revealed that the constitutive transcription of IFN-is inhibited in HPV-positive keratinocytes, which is consistent with recent in situ analyses of HPV-positive biopsy specimen material and findings in HPV-positive cervical cancer cells (12,37). Since a good correlation between ISGs reduced in HPV-positive cells (Table 1) and ISGs induced by IFN-in HPV18-positive cells can be observed, we postulate that the major cause for the reduction of ISGs in HPV-positive cells is the inhibition of IFN-transcription.…”
Section: Discussionsupporting
confidence: 92%
“…Classical type I IFNs such as IFN-␣s and IFN-␤, as well as type III IFNs, are strongly induced upon virus infection, which activates pattern recognition receptor pathways. In contrast, IFN-and IFN-ε are constitutively expressed in a cell type-specific manner and are only very moderately induced by pattern recognition receptor pathways, indicating a different way of regulation (13)(14)(15)(16)48). Recent studies demonstrated that IFN-expression is inhibited by hr-HPV both in tissue culture and in vivo (13,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IFN-and IFN-ε are constitutively expressed in a cell type-specific manner and are only very moderately induced by pattern recognition receptor pathways, indicating a different way of regulation (13)(14)(15)(16)48). Recent studies demonstrated that IFN-expression is inhibited by hr-HPV both in tissue culture and in vivo (13,15,16). It had been previously shown that IFN-␤ inhibits the growth of cells lines that maintain replicating HPV16 or -31 genomes (4,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, knockdown of STING moderately reduced IFN-expression in primary human KC, and both proteins were reduced in HPV-positive cervical tissue and CIN1 (60). IFN-downregulation in HPV-positive precursor lesions and cervical cancer has been observed before (64,65). Interestingly, De Carlo et al (65) found that while IFN-␤ and IFN-␥ mRNAs were detectable in HPV16-positive cervical epithelium from LSIL, high-grade squamous intraepithelial lesion, and carcinoma biopsy specimens, IFN-mRNA was absent.…”
Section: Kc As Mediators Of Innate Immunitymentioning
confidence: 87%